A Descriptive Account on Monitoring Public Opinion in USA: Nixon’s Administration and the Hidden Practices in Manipulating Communities - Benelmouaz, Ahmed; Seddiki, Mohamed Cherif (University of Ammar Theledji -Laghouat, 2022)
The manipulation of public opinion has been under the scope of researchers for a long time due to its importance to politicians and citizens as well. The goal of conducting this study is to make the readers aware of the methods that governments utilize to shape their opinion concerning sensitive issues as wars. In order to conduct this research, I have used the qualitative approach, since it suits my research topic. In addition, I relied on the existing data, including books, journals, magazines, articles, and websites. Furthermore, I have used exploratory analysis on the data to come up with the results of the study, and I have also synthesized the data. Consequently, our results proved that the Nixon’s administration used numerous ways in order to manipulate the public opinion during the Vietnam War. The methods included propaganda, pro-war songs, and pro-war movies, creating enemy, private groups, political oppression, and misinformation. Moreover, the research also proved that Nixon’s administration used the public opinion to design its electoral campaign in 1968, withdraw from the Vietnam War, and to resign from the presidency. The rationale of Nixon’s manipulation was to keep the public support for the war and to win the re-elections of 1972. The methodology of President Richard Nixon contained a lot of unconstitutional decisions and attitudes like using police brutality in order to reach his goals